2014
DOI: 10.4103/2230-8210.131191
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of diabetes in urban and rural India: The Indian Council of Medical Research India Diabetes Study (Phase I): Indian Council of Medical Research India Diabetes 4

Abstract: Background:Representative data on knowledge and awareness about diabetes is scarce in India and is extremely important to plan public health policies aimed at preventing and controlling diabetes.Aim:The aim of the following study is to assess awareness and knowledge about diabetes in the general population, as well as in individuals with diabetes in four selected regions of India.Materials and Methods:The study subjects were drawn from a representative sample of four geographical regions of India, Chandigarh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
76
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 14 publications
17
76
2
Order By: Relevance
“…Most of the studies have depicted a direct relation between knowledge about DM and the level of education (Babaee et al, 2007;Bruce, Davis, Cull, & Davis, 2003;Çaliskan, Ozdemir, Ocaktan, &Idil, 2006;Deepa et al, 2014;Fezeu, et al, 2010;Murugesan et al, 2007) but contrary findings were obtained from the study conducted by Ulvi et al (2009). Fezeu et al(2010) and Ulvi et al (2009) found that the family history of DM played an important role in the awareness of DM.…”
Section: Educational Status Family History Gender and Agementioning
confidence: 90%
See 3 more Smart Citations
“…Most of the studies have depicted a direct relation between knowledge about DM and the level of education (Babaee et al, 2007;Bruce, Davis, Cull, & Davis, 2003;Çaliskan, Ozdemir, Ocaktan, &Idil, 2006;Deepa et al, 2014;Fezeu, et al, 2010;Murugesan et al, 2007) but contrary findings were obtained from the study conducted by Ulvi et al (2009). Fezeu et al(2010) and Ulvi et al (2009) found that the family history of DM played an important role in the awareness of DM.…”
Section: Educational Status Family History Gender and Agementioning
confidence: 90%
“…The prevalence of risk behaviour for DM included tobacco and alcohol use, diet, and physical inactivity among select participants (Singh, Milton, Nanaiah, Samuel & Thomas, 2012). It needs to be noted that obesity was not reported as a risk factor for DM by the majority of participants (Deepa et al, 2014).…”
Section: Knowledge About Dmmentioning
confidence: 92%
See 2 more Smart Citations
“…Many LMICs, particularly in rural settings, lack the personnel and properly equipped clinics needed to provide specialized care [31,32]. Additionally, public awareness of diabetes status and management is low, and many clinics and patients cannot afford diabetes treatment [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%